Analysis of the influence of teamwork and job training on work productivity with organizational commitment as an intervening variable at KPP Pratama Semarang Barat - Siti Kamiati; Yuli Budiarti; Djoko Santoso (Jurnal Scientia, 2024)
The research problem was how to maximize employee productivity by utilizing the organizational commitment variable as an intervention in the West Semarang KPP. The research object was the West Semarang Tax Service Office, where the phenomenon of organizational performance value (NKO) and the research gap issue were found. The purpose of the study is to examine how job training and teamwork affect productivity at work, using organizational commitment as an intervening variable.Using a sampling technique called the census method, which included all 117 West Semarang KPP Pratama personnel (leaders and researchers excluded), the study's sample consisted of 117 respondents. employing smartpls software for data analysis.The test findings demonstrate that organizational commitment is positively and significantly impacted by cooperation, Teamwork has a positive and significant impact on work productivity; work training has a significant positive impact on work productivity; and organizational commitment has a significant positive impact on work productivity. These findings are supported by research. The mediation effect test revealed that organizational commitment, an intervening variable, allowed cooperation to boost productivity at work. By using organizational commitment as an intervening variable, job training was found to be able to boost work productivity in the second mediation effect test.